The Role of Fiscal Transparency in Sustaining Growth and Stability in Latin America - Parry, Taryn (IMF Working Papers; Working Paper, 2007)
Latin America has experienced a resurgence in growth in recent years. However, it is also a region that has been prone to crises while growth has not delivered a significant reduction in poverty and inequality. Maintaining a strong and stable macroeconomic performance in Latin America will depend on further cuts in public debt, identification and reduction of fiscal vulnerabilities and improvements in the quality of public spending. Improvements in governance and the business environment will also aid in attracting investment. This paper draws on assessments of fiscal transparency in twelve countries in Latin America to highlight good fiscal management and improvements in fiscal transparency that might enhance the prospect for sound fiscal performance and a more favorable investment environment. This would be an important step toward sustaining stable, higher quality growth in the region.